Performance of seed germination of six different varieties of basil (Ocimum basilicum spp.) (Research, Society and Development, 2022)
Basil is an aromatic and medicinal plant that has a wide variety of species due to cross-pollination processes that influence germination and properties. In this work, germination parameters of six different basil species were evaluated in order to describe which ones have the highest germination potential. For this, the basil varieties were grown in a greenhouse at 20-25 oC, and the germination percentage was monitored for 14 days. The Weibull modeling allowed us to evaluate that the species O. basilicum var. basilicum, O. Basilicum var. purpurascens and O. basilicum minimum are those that germinate in large proportions and that O. basilicum L. cv. Genovese has an intense dormancy process. Considering the germination time, the species O. basilicum var. basilicum is the variety with the highest germination potential.